Frequency and severity of autonomic dysfunction assessed by objective hemodynamic responses and patient-reported symptoms in individuals with myasthenia gravis - Zawadka-Kunikowska, Monika; Cieślicka, Mirosława; Klawe, Jacek J.; Tafil-Klawe, Małgorzata; Kaźmierczak, Wojciech; Rzepiński, Łukasz (Frontiers in Neuroscience, 2024)
Introduction Myasthenia gravis (MG), a rare autoimmune disorder, poses diagnostic and management challenges, with increasing incidence in Europe and significant impact on patient quality of life. Despite prevalent autonomic symptoms, comprehensive assessments integrating subjective and objective measures are lacking. We aimed to investigate the prevalence and severity of autonomic dysfunction in patients with MG and healthy controls (HCs). Materials and methods We used beat-to-beat hemodynamic responses during standardized autonomic function tests (AFTs) and the Composite Autonomic Symptom Score 31 (COMPASS-31) questionnaire. Study participants including, 53 patients with MG and 30 age- and sex matched HCs underwent standardized cardiovascular AFTs and completed the COMPASS-31 questionnaire. Patients were categorized into Non-CAN and CAN groups based on their Cardiovascular Autonomic Neuropathy (CAN) status, as evaluated using the Composite Autonomic Scoring Scale (CASS). During the AFTs, cardiovascular parameters including heart rate, systolic blood pressure (BP), diastolic BP, mean BP, stroke volume (SV), cardiac output (CO), and total peripheral resistance (TPR) were measured. Results Twenty patients with MG (38%) exhibited mild CAN (CASS ≥2) with a median total CASS score of 1.00 and CASS 0.00 in HCs. Adrenergic impairment was observed in 27 patients (52%), with 13 patients (24.5%) exhibiting longer pressure recovery time after Valsalva maneuver (VM). Cardiovagal impairment was evident in 71% of patients, with abnormal results observed in 39.6% for the deep breathing test and 56.6% for the VM. CAN MG showed worse scores than HCs for the total COMPASS-31 (p < 0.001), orthostatic (OI) (p < 0.001), secretomotor (p = 0.004), and pupillomotor domains (p = 0.004). Total COMPASS-31 and OI scores were correlated with worse disease outcomes (disease duration, severity), hemodynamic parameter changes (SV, CO, TPR) during phase II late of VM, and with changes (Δtilt-supine) in Δsystolic BP, Δdiastolic BP, Δmean BP, ΔTPR during head-up-tilt test, but not with CASS score. Conclusion Our findings demonstrate mild cardiovascular autonomic impairment in adrenergic and cardiovagal domains in patients with MG. Additionally, patient-reported autonomic symptoms correlated with hemodynamic changes during AFTs and worse disease outcomes and not with the grade of autonomic abnormalities. Incorporating beat-to-beat hemodynamics during AFTs may offer further insights for characterizing orthostatic intolerance symptoms in MG group.